An improved approach to estimate the avidity index of immunoglobulins: Evaluation of the method using IgG anti-Toxoplasma gondii - Garcia, Valeria Soledad (2018)
The daily clinical practice frequently force physicians to make adecision of whether a patient is coursing an infectious disease at theacute or the chronic stage, since treatment may be different dependingon it. This is the case of toxoplasmosis, a worldwide disease caused bythe intracellular parasite Toxoplasma gondii. When a pregnant woman isinfected for the first time by T. gondii and is not treated, the parasite cancross the placenta and severely affect the fetus. In case of primary infection,the treatment protocol includes using antiparasitic drugs toprevent serious damages, including death of the unborn baby. However,antiparasitic chemicals have side effects that should be avoided, unlesstreatment is mandatory. That is why discrimination between long-termand primary T. gondii infection turns out to be critical in infectedpregnant women (Montoya and Remington, 2008).In this work we have used rP22a, an acute-phase recombinant protein werecently described (Costa et al., 2017), to assess anti-T. gondii IgG AI,calculated by two new easier approaches, one based on the area underthe avidity curve (AUAC) and the other one based on the E-P titrationmethod with minor variations. We compare our results with those obtainedwhen calculating the AI by the conventional methods abovementioned, and the performance to render a proper sample classificationas compared to that obtained having used a commercial kit asstandard.